Antibacterial Effect of the Combination of Probiotic Milk and Calliandra Honey against Streptococcus Mutans that Causes Tooth Cavities - Uswatun Chasanah (R.K. Sharma, Institute of Medico-Legal Publications, 2020)
Background: Streptococcus mutans is a Gram-positive bacterium found in the oral cavity. As a cariogenic bacterium, Streptococcus mutans can cause dental caries through its ability to produce an acidic environment that can demineralize tooth structures so that the tooth layer is destroyed.